The Effect of Endozym β-split, a Commercial Enzyme Preparation Used for Aroma Release, on Tannat Wine Glycosides - Cid, A.G.; Goldner, M.C.; Daz, M.; Ellenrieder, G. (South African Journal of Enology and Viticulture, 2016)
Commercial preparations with glycosidase activities are used to enhance wine aroma, but they are not extensively characterized. The aim of this work was to study the effect of three enzymes on aroma improvement in Tannat red wine. After the selection of the most appropriate enzyme for further testing, its effectiveness on the hydrolysis of the total glycosides present in Tannat wine was measured. The three preparations showed high β-glucosidase and α-arabinosidase activities (in the range of 10 to 174 U/mL or U/g), but very low levels of α-rhamnosidase (less than 1 U/mL). The β-glucosidases studied remained active in the presence of Tannat wine. The selected enzyme, Endozym β-split, supplemented with α-rhamnosidase, resulted in almost 30% hydrolysis of the glycosides in Tannat wine, when added at a concentration higher than that recommended by the manufacturers. A sensory evaluation showed that the enzyme-treated wines were significantly different from the controls, suggesting that at least a part of the hydrolyzed glycosides in the Tannat wine were aroma precursors. However, it cannot be assumed that all commercial enzymes would be effective in hydrolyzing aroma precursors just because they show glycosidase activities. Higher concentrations of Endozym β-split than that recommended by the manufacturer are necessary to reach an appreciable level of glycoside hydrolysis. Supplementation of Endozym β-split with α-rhamnosidase is recommended in this enzyme – wine system for the greater release of the aroma from the glycosidicallybound precursors.